2012
DOI: 10.1001/archoto.2011.214
|View full text |Cite
|
Sign up to set email alerts
|

Qualities of Residency Applicants<subtitle>Comparison of Otolaryngology Program Criteria With Applicant Expectations</subtitle>

Abstract: Although PDs and PAs agree on the least important criteria for ranking otolaryngology residency candidates, they disagree on the most important criteria. This information provides insight into how programs select residency candidates and how this compares with applicant expectations. Furthermore, this information will assist applicants in understanding how they might be evaluated by programs. Improved understanding of the match process may increase the likelihood of having a good fit between otolaryngology pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
43
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(45 citation statements)
references
References 24 publications
(22 reference statements)
1
43
1
Order By: Relevance
“…2,4,5 This survey suggests that this same disparity in perception of the most important criteria in ranking pediatric otolaryngology fellowship applicants may occur. Although applicants believed that the interview should be the most important factor, fellowship program directors may rely more on trusted recommendations from colleagues who have interacted with applicants during their residency.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…2,4,5 This survey suggests that this same disparity in perception of the most important criteria in ranking pediatric otolaryngology fellowship applicants may occur. Although applicants believed that the interview should be the most important factor, fellowship program directors may rely more on trusted recommendations from colleagues who have interacted with applicants during their residency.…”
Section: Discussionmentioning
confidence: 86%
“…However, the factors that medical students considered most important in ranking otolaryngology residency programs were recently evaluated. 2 In an anonymous survey, program directors and medical students were asked to rank criteria important in choosing a residency candidate and how candidates should be ranked. Program directors considered the interview and personal knowledge of the applicant to be the most important criteria, whereas student applicants perceived the interview and letters of recommendation to be the most important criteria.…”
mentioning
confidence: 99%
“…Many studies have shown that higher USMLE scores increases an applicant’s chances of matching into surgical specialties 5,6,9 and surveys of applicants and program directors in Otolaryngology have also shown that both parties believe USMLE scores are one of the most important criteria used by residency programs when ranking applicants 10 . We similarly found that Step 1 scores had an impact on matching.…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13][14][15][16][17][18][19][20] The interview may also identify negative applicant characteristics such as anxiety or aggression. 21 Candidates value the interview process highly, 22,23 and cite the quality of interactions with the program director 24 and, most important, with the residents [25][26][27] during the interview as important in their decision making. Applicants value the interaction with residents during an interview to assess resident morale, 28 esprit de corps, 29 and program ''red flags'' as perceived by applicants.…”
Section: Introductionmentioning
confidence: 99%